MPLEMENTATION AND EFFORTS OF TEACHERS OF ISLAMIC EDUCATION IN EMBEDDING MULTICULTURAL VALUES IN PEMATANGSIANTAR CITY PUBLIC HIGH SCHOOL - Saidah Nur Nasution (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The objectives of this study are: (1) to find out the implementation andefforts of Islamic religious education teachers in instilling multiculturalvalues in Pematangsiantar City Public High School, (2) to find out whatare the multicultural values in Pematangsiantar City Public High School, and ( 3) to find out what are the supporting and inhibiting factors in instilling multicultural values in Pematangsiantar City High School. Thestudy was conducted at Pematang City State High School, with themethod used was a qualitative research method. Research findings showmulticultural values in Pematangsiantar City Public High School byIslamic religious education teachers through daily teaching and learningactivities, by integrating them into existing subject matter, which has beenarranged in the curriculum of Islamic religious education learninglearning, syllabus and programs learning programs from government andschools.